An experimental assessment of internal variables constitutive models for viscoelastic materials. (January 2015) - Borges, F.C.L.; Castello, D.A.; Magluta, C.; Rochinha, F.A.; Roitman, N.
Abstract: The present work is aimed at presenting an experimental assessment of a constitutive model used to describe viscoelastic behavior. This strategy is built on the basic principles of the Verification and Validation (V&V) philosophy. The mechanical model used to describe the viscoelastic behavior is a constitutive one based on the concept of internal variables. The parameter estimation of the model is performed using frequency domain data through the Particle Swarm Optimization algorithm. A set of different experimental set-ups were built in order to span the structural operational domain from which data can be measured. The model validation is performed based on the use of validation metrics which take into account uncertainties both in the model predictions and observed data. Highlights: Three different experimental set-ups were built for model calibration and validation. Model validation analyses are performed using basic principles of V&V and validation metrics. The validation metrics take into account both model and measured data uncertainties. We analyze the effect of model uncertainties along the validation processes. We analyze uncertainties due to mounting and dismounting the experimental set-ups.